Comparative Study of Internet Usage Among University Students: A Study of the University of Dhaka, Bangladesh - Hossain, Md. Akram; Rahman, Md. Habibur (European Scientific Journal, ESJ, 2017)
Internet is a versatile tool used by the students that draws attention of many researchers. But little research has been found regarding the comparative study of internet usage among university students. For this reason, the study surveyed the internet usage among university students coming from Business Studies, Science & Arts disciplines at University of Dhaka, Bangladesh and the overall perceptions towards the internet usage. So we developed a survey questionnaire and collected data on students’ demographics, internet usage behavior and purposes of internet use. Therefore, we distributed 50 questionnaires to each discipline and a total of 150 questionnaires were returned and all were usable. Then we analyzed the obtained data using SPSS. The results show that the percentage of internet usage among the students coming from Business Studies, Science and Arts disciplines is 100%, 92% and 90% respectively. The study recommends that the students coming from Science and Arts background should enhance the internet usage. And the students from all backgrounds should enhance the frequency of internet access per day and invest more on internet usage. The study also recommends that the universities should provide adequate internet facilities and enabling environment for student. This study provides a theoretical and empirical basis for further studies on internet usage of university students.